Data processing pipeline for cardiogenic shock prediction using machine learning - Jajcay, Nikola; Bezak, Branislav; Segev, Amitai; Matetzky, Shlomi; Jankova, Jana; Spartalis, Michael; El Tahlawi, Mohammad; Guerra, Federico; Friebel, Julian; Thevathasan, Tharusan; Berta, Imrich; Pölzl, Leo; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Recent advances in machine learning provide new possibilities to process and analyse observational patient data to predict patient outcomes. In this paper, we introduce a data processing pipeline for cardiogenic shock (CS) prediction from the MIMIC III database of intensive cardiac care unit patients with acute coronary syndrome. The ability to identify high-risk patients could possibly allow taking pre-emptive measures and thus prevent the development of CS. Methods: We mainly focus on techniques for the imputation of missing data by generating a pipeline for imputation and comparing the performance of various multivariate imputation algorithms, including k-nearest neighbours, two singular value decomposition (SVD) - based methods, and Multiple Imputation by Chained Equations. After imputation, we select the final subjects and variables from the imputed dataset and showcase the performance of the gradient-boosted framework that uses a tree-based classifier for cardiogenic shock prediction. Results: We achieved good classification performance thanks to data cleaning and imputation (cross-validated mean area under the curve 0.805) without hyperparameter optimization. Conclusion: We believe our pre-processing pipeline would prove helpful also for other classification and regression experiments.